Identifying Geographic Disparities in the Early Detection of Breast Cancer Using a Geographic Information System - Luxme Hariharan; Ronald E. Gangnon, PhD; Patrick L. Remington, MD; Jane A. McElroy, PhD; LeAnn D. Andersen, MS (Centers for Disease Control and Prevention, 2006)
IntroductionIdentifying communities with lower rates of mammography screening is a critical step to providing targeted screening programs; however, population-based data necessary for identifying these geographic areas are limited. This study presents methods to identify geographic disparities in the early detection of breast cancer.MethodsData for all women residing in Dane County, Wisconsin, at the time of their breast cancer diagnosis from 1981 through 2000 (N = 4769) were obtained from the Wisconsin Cancer Reporting System (Wisconsin's tumor registry) by ZIP code of residence. Hierarchical logistic regression models for disease mapping were used to identify geographic differences in the early detection of breast cancer.ResultsThe percentage of breast cancer cases diagnosed in situ (excluding lobular carcinoma in situ) increased from 1.3% in 1981 to 11.9% in 2000. This increase, reflecting increasing mammography use, occurred sooner in Dane County than in Wisconsin as a whole. From 1981 through 1985, the proportion of breast cancer diagnosed in situ in Dane county was universally low (2%-3%). From 1986 through 1990, urban and suburban ZIP codes had significantly higher rates (10%) compared with rural ZIP codes (5%). From 1991 through 1995, mammography screening had increased in rural ZIP codes (7% of breast cancer diagnosed in situ). From 1996 through 2000, mammography use was fairly homogeneous across the entire county (13%-14% of breast cancer diagnosed in situ).ConclusionThe percentage of breast cancer cases diagnosed in situ increased in the state and in all areas of Dane County from 1981 through 2000. Visual display of the geographic differences in the early detection of breast cancer demonstrates the diffusion of mammography use across the county over the 20-year period.